Push and Pull: Disability Insurance, Regional Labor Markets, and Benefit Generosity in Canada and the United States - Milligan, Kevin; Schirle, Tammy (Journal of Labor Economics, 2019)
Disability insurance take-up has expanded substantially in the past 20 years in the United States while shrinking in Canada. We empirically assess these trends by measuring the strength of the “push” from weak labor markets versus the “pull” of more generous benefits. Using an instrumental variables strategy comparing benefit changes across country, age, and year, we find that both benefits and regional wages matter. Simulations suggest that the upswing in disability insurance take-up in the United States would be reversed, dropping the caseload by 41% if benefits and wages had followed the growth path observed in Canada.